2021
DOI: 10.4252/wjsc.v13.i4.260
|View full text |Cite
|
Sign up to set email alerts
|

Calcium channels and their role in regenerative medicine

Abstract: Stem cells hold indefinite self-renewable capability that can be differentiated into all desired cell types. Based on their plasticity potential, they are divided into totipotent (morula stage cells), pluripotent (embryonic stem cells), multipotent (hematopoietic stem cells, multipotent adult progenitor stem cells, and mesenchymal stem cells [MSCs]), and unipotent (progenitor cells that differentiate into a single lineage) cells. Though bone marrow is the primary source of multipotent stem cells in adults, oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 143 publications
0
8
0
Order By: Relevance
“…The principal tissue reservoir of mammalian adult stem cells is the bone marrow. However, other sources are skin, placenta, adipose tissue and umbilical cord, where these stem cells, especially MSCs, proliferate and differentiate and heal the spoiled tissue during injury [91]. Self-renewal and differentiation requirements drive stem cells' capacity that is dependent on their ability to have adequate autophagic processes [92].…”
Section: Autophagy/apoptosis and Stem Cell Functionmentioning
confidence: 99%
“…The principal tissue reservoir of mammalian adult stem cells is the bone marrow. However, other sources are skin, placenta, adipose tissue and umbilical cord, where these stem cells, especially MSCs, proliferate and differentiate and heal the spoiled tissue during injury [91]. Self-renewal and differentiation requirements drive stem cells' capacity that is dependent on their ability to have adequate autophagic processes [92].…”
Section: Autophagy/apoptosis and Stem Cell Functionmentioning
confidence: 99%
“…Mammalian bone marrow is recognized as the largest reservoir of adult stem cells and a variety of stem cells, including hematopoietic stem cells (HSCs), mesenchymal stem cells (MSCs), multipotent adult progenitor cells (MAPCs), and even small embryonic-like stem cells (VSELs) ( Ahamad and Singh, 2021 ). Though bone marrow is the primary source of MSCs in adults, other tissues such as adipose tissues, placenta, amniotic fluid, umbilical cord blood, periodontal ligament, and dental pulp also harbor MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Though bone marrow is the primary source of MSCs in adults, other tissues such as adipose tissues, placenta, amniotic fluid, umbilical cord blood, periodontal ligament, and dental pulp also harbor MSCs. However, bone marrow still remains the most common and consistently trustworthy source for in vitro studies, including isolation, culture, propagation, and characterization ( Ahamad and Rath, 2019 ; Ahamad and Singh, 2021 ). In addition, recent research has revealed that stem cells do not remain static, and their properties, including surface marker expression and stem cell potential, are decreased as they are passaged and in aged animals.…”
Section: Discussionmentioning
confidence: 99%
“…In embryonic and human mesenchymal stem cells, calcium entry into the cytoplasm from the extracellular space is mediated mainly by store-operated Ca 2+ channels rather than the voltage-gated calcium channels (VGCCs) or by the Na + /Ca 2+ exchangers. 11 The mechanism of calcium entry seems to be different in HSCs. A previous study found that suppression of intracellular Ca 2+ level into HSCs by Nifedipine (blockers of L-type voltage-gated Ca 2+ channels) abolished the resultant mitochondrial activation and prolonged cell division interval in HSCs, and simultaneously achieved both cell division and HSC maintenance.…”
mentioning
confidence: 99%
“…In embryonic and human mesenchymal stem cells, calcium entry into the cytoplasm from the extracellular space is mediated mainly by store-operated Ca 2+ channels rather than the voltage-gated calcium channels (VGCCs) or by the Na + /Ca 2+ exchangers 11 . The mechanism of calcium entry seems to be different in HSCs.…”
mentioning
confidence: 99%